ANALYSIS OF THE EXPLOITATION PROPERTIES OF CONCRETE UNDER THE INFLUENCE OF MOIST ENVIRONMENTS - Safarova Ruxshona Ulug‘bek qizi (Western European Studies, 2025)
The issue of water absorption in cement-based materials is a globally pressing problem. The water absorption resistance of concrete is primarily dependent on its composition. One of the characteristics affecting the longevity of concrete is porosity, as well as external and internal factors. However, relatively large voids reduce the strength of concrete. The permissible air content is 2-3%. Water absorption worsens the properties of materials, increases average density, and decreases strength. The effect of water, humidity, cyclic freezing and thawing on cement-based materials causes a process of corrosion, leading to the degradation of the cement stone's structure.
Keywords: humidity; capillary; concrete; cement